Theories of value and distribution since Adam Smith :ideology and economic theory. - "Dobb, Maurice." (New Delhi, 1979)
This book contains following topics: Introductory: On Ideology; Adam Smith ; David Ricardo; The Reaction against Ricardo; John Stuart Mill; Karl Marx; The Jevonian Revolution; Rekindling of Debate; A Decade of High Criticism.
Keywords: Value distribution theory